PENGARUH PEMBERIAN EKSTRAK ETANOL BUNGA KECOMBRANG (Etlingera elatior (Jack) R. M. Sm.) TERHADAP KADAR MALONDIALDEHID (MDA) MENCIT PUTIH JANTAN HIPERLIPIDEMIA - Ria - afrianti (Jurnal Penelitian Farmasi Indonesia, 2021)
Hyperlipidemia is a pathological condition caused by blood lipid abnormalities that increase blood cholesterol levels. Increased cholesterol levels in the blood will lead to increased production of free radicals resulting in stress oxidative and cause increased malondialdehyde (MDA) levels. This study was used to determine the level of MDA male white mice hyperlipidemia. Measurement of MDA levels was done by TBA (thio Barbituric Acid) reactivity test. In this research used 5 group : negative control group, positive control group, dose of extract 100 mg/kgBW group, dose of extract 200 mg/kgBW group and dose of extract 400 mg/kgBW group. The mean values ​​of MDA levels of negative group : 2,40 nmol/ml, positive group : 4,19 nmol/ml, dose 100 mg/kgBW group : 3,67 nmol/ml dose 200 mg/kgBW group : 2.59 nmol/ml and dose 400 mg/kgBW group : 2.47 nmol/ml. The mean value of MDA group dose of 200 mg/kgBW and 400 mg/kgBW was significantly (p<0.05) approach to the average MDA value of the negative control group. So it can be concluded the administration of ethanol extract of kecombrang flowers can decrease MDA levels of hyperlipidemic male white mice.